(untitled) (INNOTEC, 2017)
A diversity of environments, stakeholders, interests and socioenvironmental problems converge in the basin of the El Potrero stream, Maldonado department, Uruguay. The objective of this article is to outline management proposals for conflicts, problems and socioenvironmental opportunities in this area, applying the Integrated Coastal Management (ICM) approach. The ICM promotes a balance between social, environmental, and economic interests in the coastal zone, based on an ecosystem approach and involving the different community stakeholders in the process. Based on document reviews, interviews with 11 local actors, internal team workshops, and an open validation workshop, four issues were identified to focus the management proposals: strengthening governance, promoting the environmental integrity of the seaside coast, conserving the stream and its margins, and fostering urbanization with a low environmental impact. Each management issue gave rise to a program from which projects with specific actions emerged. All programs are grouped in an "Integrated Management Plan for the Lower Basin of the El Potrero Stream". The exchange between different actors favored the relationship between stakeholders and showed the potential for working together.